Ergonomics risk among computer user of Universiti Utara Malaysia students - Saimat, Siti Nazuah; Nawi, Nur Syazwani (Universiti Utara Malaysia, 2020)
Ergonomics risk factors are about the situation that can make people get pain. It refers to an accidental or deliberate situation that is contrary to ergonomic principles that can provide comfort to a person and might harmful to the health and well-being of the person during computer usage. This study is conducted to investigate the level knowledge of students on ergonomics computer and to help students to identify ergonomics risk factors associated with musculoskeletal discomfort and symptoms exists due to the use of computers. This study was conducted by using the quantitative method and 152 of the sample were randomly selected. Descriptive statistic of frequency and percentage was used in all data while T-test and ANOVA analysis was used to identify level knowledge on ergonomics computer based on gender.